MATEC Web of Conferences - Kvesko; Kornienko economist Associate Professor of Tomsk Polytechnic University, Doctor of Philosophy; Kvesko; Chicherina Linguist Associate Professor of Tomsk Polytechnic University, Candidate of pedagogical sciences (2018)
The paper discusses the intelligent information systems as expert systems to meet the challenges of management in the knowledge society. These allow optimization of decision-making and simulation of the human and society activities. The focus is made on the relation between the information structure and globalization. It is emphasized that the information structure becomes the basis of public life functioning, which is based on complex industry of information processing through information technologies. Modern management approach focuses on the "strategy" construct. The latter allows timely and adequate effect. This adequacy, in turn, makes it possible to determine the long-term development of an object. The strategy appears to be optimal if it is supported by resources. Using innovations solves the problem of prediction of generated knowledge. An innovation system is able to initiate transformations in the knowledge system. The tasks solved by the expert systems involve the tasks of combined type, namely the tasks of learning, forecasting and monitoring that ensures forecast completeness, which employs a parametric dynamic model.